2021
DOI: 10.1007/s00011-021-01505-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin 6 -174 G/C polymorphism with coronary artery disease and circulating IL-6 levels: a systematic review and meta-analysis

Abstract: Introduction Circulating IL-6 levels and at least one polymorphic form of IL6 gene (IL6 -174 G/C, rs1800795) have been shown to be independently associated with coronary artery disease (CAD) by several investigators. Despite more than 12 published meta-analyses on this subject, association of -174 G/C with CAD, especially amongst distinct ancestral population groups remain unclear. We, therefore, conducted a systematic review and an updated meta-analysis to comprehensively ascertain the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 77 publications
(84 reference statements)
1
5
1
Order By: Relevance
“…Recent systematic reviews with meta-analysis have shown that the CC homozygous genotype is an unfavorable genotype that increases susceptibility to coronary artery disease [5,6]. These findings are consistent with a previous prospective, population-based study (Rotterdam Study) that found greater arterial stiffness as a precursor to cardiovascular disease in individuals with the CC genotype compared to individuals with the wild-type GG genotype [7].…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Recent systematic reviews with meta-analysis have shown that the CC homozygous genotype is an unfavorable genotype that increases susceptibility to coronary artery disease [5,6]. These findings are consistent with a previous prospective, population-based study (Rotterdam Study) that found greater arterial stiffness as a precursor to cardiovascular disease in individuals with the CC genotype compared to individuals with the wild-type GG genotype [7].…”
Section: Introductionsupporting
confidence: 87%
“…It is consistent with a previous study [33] in which the -174 CC genotype (compared to the GG genotype) was associated with higher susceptibility to upper respiratory tract infections among endurance athletes. In contrast, IL-6-174 GG homozygous carrier status has already been linked to reduced susceptibility to acute and chronic inflammatory diseases [5,6,34,35]. On the other hand, the decrease in circulating TNFα after 12-week swimming training in our study, which was observed in the whole ST group, but not in the CON group, was related to both GG and CC genotypes within IL-6-174G/C SNP.…”
Section: Discussioncontrasting
confidence: 71%
“…The rs1800795 polymorphism in the promoter region of IL6 gene is one of the most widely analyzed in cardiovascular diseases. A recent meta-analysis examined more than 40 studies related to rs1800795, with the firm conclusion that there is a clear association with coronary artery disease driven, at least in part, by upregulating plasma IL-6 levels ( 21 ). The hypothesis in that study is that carriers of the C allele, through various mechanisms not yet fully clarified, have upregulated transcription and translation of the gene.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, PALMD is not released to the circulation. 1 By contrast, we investigated whether the IL6 polymorphism could have an effect on the circulating levels of the cytokine in our patients, as it is described for coronary artery disease (21), by measuring IL-6 levels in 76 serum samples selected according to rs1800795 genotype. The CC genotype was associated with higher levels of serum IL-6 (23.5 pg/ml vs. 10.5 pg/ml for the other genotypes; P = 0.006) (Figure 3), even after adjustment for age, hypertension and coronary artery disease (estimate: 13.92, 95% CI 2.16-25.68, P = 0.021).…”
Section: Il6 Genotype Is Associated With Circulating Levels Of Il-6mentioning
confidence: 99%
“…The current research on IL-6 gene polymorphism mainly focuses on SNPs in the promoter region, such as −597G/A (re1800797), −572G/C (rs1800796), −174G/C (rs1800795). They affect the expression level of IL-6 by regulating gene transcription and expression strength, and then make differences in the susceptibility of the population to diseases such as COVID-19, 7 coronary artery disease, 8 and type 2 diabetes. 9 IL-6 polymorphism has been reported to be involved in bone loss, 10 fracture, 11 and osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%